Treatment of a Femur Nonunion with Microsurgical Corticoperiosteal Pedicled Flap from the Medial Femoral Condyle. (15th March 2016) - Guzzini, Matteo; Calderaro, Cosma; Guidi, Marco; Civitenga, Carolina; Ferri, Germano; Ferretti, Andrea
Abstract : Introduction . The vascularized corticoperiosteal flap is harvested from the medial femoral condyle and it is nourished by the articular branch of the descending genicular artery and the superomedial genicular artery. This flap is usually harvested as a free flap for the reconstruction of bone defects at forearm, distal radius, carpus, hand, and recently at lower limb too. Case Report . A 50-year-old Caucasian man referred to our department for hypertrophic nonunion of the distal femur, refractory to the conservative treatments. The first surgical choice was the revision of the nail and the bone reconstruction with a corticoperiosteal pedicled flap from the medial femoral condyle. We considered union to have occurred 3.5 months after surgery when radiographs showed bridging of at least three of the four bony cortices and clinically the patient was able to walk with full weight bearing without any pain. At the last follow-up (25 months), the patient was completely satisfied with the procedure. Discussion . The corticoperiosteal flap allows a faster healing of fractures with a minimal morbidity at the donor site. We suggest that the corticoperiosteal pedicled flap graft is a reliable and effective treatment for distal femur nonunion.